2000
DOI: 10.1103/physrevlett.84.4405
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Symmetry Breaking in Crystallization: The Role of Convection

Abstract: Chiral symmetry breaking in stirred crystallization of sodium chlorate ( NaClO3) occurs via the production of secondary crystals from a single "mother crystal." Martin, Tharrington, and Wu [Phys. Rev. Lett. 77, 2826 (1996)] investigated this phenomenon and concluded that it was mechanical crushing of a crystal by the stir bar, not convection, that produces secondary crystals from a single crystal. Here we report the generation of secondary crystals of sodium chlorate when a saturated solution of sodium chlorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 18 publications
1
97
0
Order By: Relevance
“…They concluded that this occurs because, in their experimental conditions, at 6°C of supercooling the solution is at or very close to the critical supercooling temperature for spontaneous primary nucleation and that only at moderate supercooling, avoiding primary nucleation, the effect of the seeding can be real in the symmetry breaking process. This necessity of a low supersaturation level for symmetry breaking in the hypothesis of a first "mother crystal", is admitted by Kondepudi et al [4] when explaining the experimental results of Martin et al [10]. These results indicate that a very rapid crystallization leading to formation of large number of crystal nuclei, should result in an equal number of 1 and d crystals (no symmetry break ing).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…They concluded that this occurs because, in their experimental conditions, at 6°C of supercooling the solution is at or very close to the critical supercooling temperature for spontaneous primary nucleation and that only at moderate supercooling, avoiding primary nucleation, the effect of the seeding can be real in the symmetry breaking process. This necessity of a low supersaturation level for symmetry breaking in the hypothesis of a first "mother crystal", is admitted by Kondepudi et al [4] when explaining the experimental results of Martin et al [10]. These results indicate that a very rapid crystallization leading to formation of large number of crystal nuclei, should result in an equal number of 1 and d crystals (no symmetry break ing).…”
Section: Resultsmentioning
confidence: 54%
“…On the other hand, secondary nucleation is the process by which a "mother crystal" generates secondary crystals at a fast rate if the solution is stirred; in the case of NaCI03, a first lord "mother crystal" generates new crystals with similar chirality in a few minutes. The sequence of events is as follows [3,4]: a single crystal randomly nucleates at some time by primary nucleation and begins to grow. When the crystal reaches a critical size it begins to produce secondary nuclei, which have the same chirality as their "mother".…”
mentioning
confidence: 99%
“…This scenario may apply to amino acids whose crystallization is known to purify the material from water [27] and make the reaction of polymerization more probable. High cooperativity of crystallization could have been the reason for the appearance of biochirality because dendritic crystallization is also known to enhance the SCSB mechanism through fragmentation [11,22,23]. Periodic temperature variations, e.g.…”
Section: Scenarios Of the Origin Of Biological Materialsmentioning
confidence: 99%
“…Kondepudi et al [20,21] and Buhse et al [22] demonstrated the mechanism of spontaneous chiral symmetry breaking (SCSB), where cooling and stirring of highly concentrated aqueous solution of achiral molecules, e.g. sodium chlorate, yields chiral crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon has been investigated both experimentally and theoretically (McBride & Carter 1991;Kondepudi et al, 1995 a,b;Kondepudi et al, 1993;Kondepudi et al, a,1995Kondepudi & Sabanayagam, 1994;Qian & Botsaris, 1998, 2004. At present, efforts are made to establish the experimental conditions under which the phenomenon occurs, to determine all important parameters controlling its kinetics and mechanisms, and to develop a reliable theory (Veintemillas-Verdaguer et al, 2007;Viedma 2004;Cartwright et al, 2004;Martin et al , 1996;Metcalfe & Ottino, 1994;Bushe et al, 2000). Our results for sodium chlorate have shown that even in unstirred solutions there is a finite probability of creation of large enantiomeric excess (Szurgot & Szurgot, 1995a) and pure enantiomeric forms (Szurgot & Szurgot, 1995b), what means that chiral symmetry is broken in sodium chlorate unstirred crystallization.…”
Section: Introductionmentioning
confidence: 99%